Bamboozled - Blanchard, Terence 1962- (<<The>> Criterion collection, 2020)
"With this blisteringly funny, unapologetically confrontational satire, writer-director Spike Lee examined the past, present, and future of racism in American popular culture, issuing a daring provocation to creators and consumers alike. Under pressure to help revive his network’s low ratings, television writer Pierre Delacroix (Damon Wayans) hits on an explosively offensive idea: bringing back blackface with The New Millennium Minstrel Show. The white network executives love it, and so do audiences, forcing Pierre and his collaborators to confront their public’s insatiable appetite for dehumanizing stereotypes. Shot primarily on unvarnished digital video and boasting spot-on performances from Wayans, Savion Glover, Jada Pinkett Smith, Tommy Davidson, Michael Rapaport, Mos Def, and Paul Mooney, Bamboozled is a stinging indictment of mass entertainment at the turn of the twenty-first century that looks more damning with each passing year." [criterion.com]
Original: USA 2000
director-approved two-DVD special edition features: new 2k digital restoration, supervised by director of photography Ellen Kuras and approved by director Spike Lee ; audio commentary from 2001 featuring Lee ; new conversation between Lee and film programmer and critic Ashley Clark ; new interviews with choreographer and actor Savion Glover, actor Tommy Davidson, and costume designer Ruth E. Carter ; "On blackface and the minstrel show", a new interview program featuring film and media scholar Racquel Gates ; "The making of Bamboozled" (2001), a documentary featuring Lee, Glover, Davidson, actors Jada Pinkett Smith, Michael Rapaport, and Damon Wayans, and other members of the cast and crew ; deleted scenes, music videos for the Mau Maus' "Blak iz blak" and Gerald Levert's "Dream with no love," and alternate parody commercials created for the film ; poster gallery and trailer ; plus an essay by Clark
Bildformat 1.77:1
Keywords: Film; DVD-Video